Fulfillment of Clean Water Needs for Households in Waeeken Village, South Buru Regency - Teslatu, Tineke; Salakory, Melianus; Leuwol, Ferdinad Salomo (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Waeeken Village in South Buru Regency faces challenges in meeting clean water needs. Although groundwater sources are a priority due to their superior quality and lower pollution impacts, accessibility, and geographical limitations are obstacles. In the dry season, people depend on clean water from rock sources, although they are difficult to reach. Research findings show that there is a high water need per family, that it exceeds 120 liters per day, and that there is a dependence on water sources with limitations. Although there are efforts to use rainwater, difficulties remain due to the distance that must be traveled. The study